TRPA1 mediates mechanical sensitization in nociceptors during inflammation. - Richard C Lennertz (Public Library of Science (PLoS), 2012)
Inflammation is a part of the body's natural response to tissue injury which initiates the healing process. Unfortunately, inflammation is frequently painful and leads to hypersensitivity to mechanical stimuli, which is difficult to treat clinically. While it is well established that altered sensory processing in the spinal cord contributes to mechanical hypersensitivity (central sensitization), it is still debated whether primary afferent neurons become sensitized to mechanical stimuli after tissue inflammation. We induced inflammation in C57BL/6 mice via intraplantar injection of Complete Freund's Adjuvant. Cutaneous C fibers exhibited increased action potential firing to suprathreshold mechanical stimuli. We found that abnormal responses to intense mechanical stimuli were completely suppressed by acute incubation of the receptive terminals with the TRPA1 inhibitor, HC-030031. Further, elevated responses were predominantly exhibited by a specific subgroup of C fibers, which we determined to be C-Mechano Cold sensitive fibers. Thus, in the presence of HC-030031, C fiber mechanical responses in inflamed mice were not different than responses in saline-injected controls. We also demonstrate that injection of the HC-030031 compound into the hind paw of inflamed mice alleviates behavioral mechanical hyperalgesia without affecting heat hyperalgesia. Further, we pharmacologically anesthetized the TRPA1-expressing fibers in vivo by co-injecting the membrane-impermeable sodium channel inhibitor QX-314 and the TRPA1 agonist cinnamaldehyde into the hind paw. This approach also alleviated behavioral mechanical hyperalgesia in inflamed mice but left heat hypersensitivity intact. Our findings indicate that C-Mechano Cold sensitive fibers exhibit enhanced firing to suprathreshold mechanical stimuli in a TRPA1-dependent manner during inflammation, and that input from these fibers drives mechanical hyperalgesia in inflamed mice.